Comparison of 1-Palmitoyl-2-Linoleoyl-3-Acetyl-Rac-Glycerol-Loaded Self-Emulsifying Granule and Solid Self-Nanoemulsifying Drug Delivery System: Powder Property, Dissolution and Oral Bioavailability - Dong Shik Kim; Jung Suk Kim; Soo-Jeong Lim; Jong Oh Kim; Chul Soon Yong; Han-Gon Choi; Sung Giu Jin (MDPI AG, 2019)
The main objective of this study was to compare the powder property, dissolution and bioavailability of 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG)-loaded self-emulsifying granule system (SEGS) and solid self-nanoemulsifying drug delivery system (SNEDDS). Various SEGS formulations were prepared, and the effect of surfactant and binder on the drug solubility in them, leading to selecting sodium lauryl sulphate (SLS) and hydroxyl propyl methyl cellulose (HPMC). The SEGS and SNEDDS were prepared with PLAG/SLS/HPMC/calcium silicate/microcrystalline cellulose at the weight ratio of 1:0.25:0.1:0.5:3 employing the fluid bed granulation and spray-drying technique, respectively. Their powder properties were compared in terms of flow ability, emulsion droplet size, scanning electron microscopy, and powder X-ray diffraction. Furthermore, the solubility, dissolution, and oral bioavailability in rats of the SEGS were assessed in comparison with the SNEDDS. The SEGS and SNEDDS enhanced the solubility of the drug approximately 36- and 32-fold as compared with the drug alone; but they had no differences. The crystalline drug may exist in both the calcium silicate and microcrystalline cellulose (MCC) in the SEGS, but only in the calcium silicate in the SNEDDS. The SEGS had considerably improved the flow ability (Hausner ratio, 1.23 vs. 1.07; Carr index, 19.8 vs. 43.5%) and drug dissolution as compared with the SNEDDS. The SEGS and SNEDDS with double peak profiles, unlike the single peak of drug alone, showed a significantly higher plasma concentration and area under the curve (AUC), as compared with drug alone. Although they were not significantly different, the SEGS gave higher AUC than did the SNEDDS, suggesting its enhanced oral bioavailability of PLAG. Thus, the SEGS could be used as a powerful oral dosage form to improve the flow ability and oral bioavailability of PLAG, an oily drug.